2010
DOI: 10.1103/physrevb.81.224511
|View full text |Cite
|
Sign up to set email alerts
|

Appearance of pressure-induced superconductivity inBaFe2As2under hydrostatic conditions and its extremely high sensitivity to uniaxial stress

Abstract: We have performed electrical resistivity measurements on single crystal BaFe2As2 under high pressure P up to 16 GPa with a cubic anvil apparatus, and up to 3 GPa with a modified Bridgman anvil cell. The samples were obtained from the same batch, which was grown with a self-flux method. A cubic anvil apparatus provides highly hydrostatic pressure, and a modified Bridgman anvil cell, which contains liquid pressure transmitting medium, provides quasi hydrostatic pressure. For highly hydrostatic pressure, the crys… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
99
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(105 citation statements)
references
References 31 publications
6
99
0
Order By: Relevance
“…2 Among 122-type materials, BaFe 2 As 2 has gained much attention as a parent compound because superconductivity can be induced in this material by various means, i.e., by applying pressure [3][4][5] and by substitutions at the Ba site (by K) 6 , at the Fe site (by Co, Ni, Ru, Rh, Pd) 2,7 and at the As site (by P). 8 An interesting result is that while electron doping by Co, Ni, Rh and Pd at the Fe site in BaFe 2 As 2 induces superconductivity, hole doping by Cr and Mn for Fe does not.…”
Section: Introductionmentioning
confidence: 99%
“…2 Among 122-type materials, BaFe 2 As 2 has gained much attention as a parent compound because superconductivity can be induced in this material by various means, i.e., by applying pressure [3][4][5] and by substitutions at the Ba site (by K) 6 , at the Fe site (by Co, Ni, Ru, Rh, Pd) 2,7 and at the As site (by P). 8 An interesting result is that while electron doping by Co, Ni, Rh and Pd at the Fe site in BaFe 2 As 2 induces superconductivity, hole doping by Cr and Mn for Fe does not.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5][6][7][8][9][10][11][12][13] They exhibit SC with external pressure only, although many other families of Fe based superconductors require some form of chemical doping or deviation from stoichiometry to exhibit SC. 1 In particular, SrFe 2 As 2 (Sr122) and BaFe 2 As 2 (Ba122) show pressure-induced SC at relatively high temperatures of T c =34 K 5,7-9 and 28 K, 4,7,9,11 , respectively.…”
mentioning
confidence: 99%
“…Namely, it has been shown that the pressure evolutions of the AFM and SC states strongly depend on the hydrostaticity. 8,11,12 Here, hydrostaticity refers to how isotropic the pressure acting on the sample is. The hydrostaticity in a high pressure experiment depends on the types of pressure cell and pressure transmitting medium used.…”
mentioning
confidence: 99%
“…2 and 4). For comparison, the superconducting temperature (T C ) was taken from previous electrical resistivity measurements using hydrostatic medium similar to our experiments (28). Below 3 GPa, the magnetic transition occurs over a narrower temperature region, and the T* curve coincides with the T S by XRD and resistivity measurements as shown in Figs.…”
Section: Resultsmentioning
confidence: 96%
“…Similar to the chemical doping, applied pressure has been found to cause the same effects on tuning the SDW state to superconductivity (23)(24)(25)(26)(27)(28). Because AFM ordering is strongly coupled with structural distortion, further investigation under controlled pressure temperature (P-T) conditions using in situ probes sensitive to these transitions is needed to unravel the intrinsic interplay between structure and magnetism in the parent compound of iron-based superconductors.…”
mentioning
confidence: 99%